A STUDY ON USAGE HABITS OF SOCIAL MEDIA OF ELEMENTARY SCHOOL STUDENTS: ELAZIG SAMPLE - Karakoc, Enderhan; Bozkurt Avci, Ikbal (Selcuk Univ, Inst Turkish Studies, 2015)
Being of vital importance of communication based on developments in technology raised interpersonal communication from face-to-face to a dimension mediated by technology. Parrticularly, due to becoming popular of personal computers and mobile phones, communication evolved to new media together with it. New functions along with traditional functions have been loaded to communication by new media technologies; receiver has started to attend to communication process faster and more effectively. Due to opportunities provided by new media/social media, more people preferred it day by day and several people from children to old persons tended towards social media. Elementary school students constitute a significant part of the society at this point. Therefore, this study aims at identifying usage habits of social media of elementary school students. In the scope of study, face-to-face interview (survey) was carried out with 400 elemantary school students in the city center of Elazig. As a result of this stiudy, it was observed that a major part of students have been using social media for a long time and there is no difference in using social media according to sexes of attendants.
Keywords: Social Media; Usage habits of social media; communication; Elazig sample